Moderasi Beragama dalam Pendidikan Multikultural: Studi Kasus Siswa Tionghoa di SMP Negeri 2 Kota Pontianak - Muhardi Muhardi; Faizal Amin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Amid the complexity of ethnic and religious diversity in public schools, religious moderation becomes essential in creating a safe and inclusive educational environment. This study aims to examine the practice of religious moderation within the context of multicultural education, focusing on the experiences of Chinese students at SMP Negeri 2 Kota Pontianak. In a multiethnic and multireligious society like Pontianak, students from minority groups often face challenges in expressing their cultural and religious identities, especially within formal educational settings dominated by majority values. The study explores how values of moderation, such as tolerance, respect for differences, and social harmony, are manifested in daily school practices. Using a qualitative approach and case study design, data were collected through observation, in-depth interviews, and documentation involving students, teachers, and school staff. The findings show that the school’s multicultural approach, implemented through curriculum content, interfaith activities, and a culture of dialogue among students, has successfully created an open space for identity expression among Chinese students. The integration of Islamic religious education with the values of religious moderation not only nurtures religiosity but also strengthens social cohesion and inclusive civic identity. This study contributes to the development of adaptive and equitable pedagogical strategies in addressing diversity in formal education.   Keywords: Religious Moderation, Multicultural Education, Chinese Students